Are depressive symptoms associated with quality of care in diabetes? Findings from a nationwide population-based study. Issue 1 (22nd March 2021) - Jung, Andreas; Du, Yong; Nübel, Julia; Busch, Markus A; Heidemann, Christin; Scheidt-Nave, Christa; Baumert, Jens
Abstract : Introduction: We investigated whether the presence of depressive symptoms among adults with diagnosed diabetes is associated with adverse quality of diabetes care. Research design and methods: The study population was drawn from the German national health survey 'German Health Update' 2014/2015-European Health Interview Survey and included 1712 participants aged ≥18 years with self-reported diabetes during the past 12 months. Depressive symptoms in the past 2 weeks were assessed by the eight-item depression module of the Patient Health Questionnaire (PHQ-8), with PHQ-8 sum score values ≥10 indicating current depressive symptoms. We selected 12 care indicators in diabetes based on self-reported information on care processes and outcomes. Associations of depressive symptoms with those indicators were examined in multivariable logistic regression models with stepwise adjustments. Results: Overall, 15.6% of adults with diagnosed diabetes reported depressive symptoms, which were higher in women than in men (18.7% vs 12.9%). Adjusted for age, sex, education, social support, health-related behaviors, and diabetes duration, adults with depressive symptoms were more likely to report acute hypoglycemia (OR 1.81, 95% CI 1.13 to 2.88) or hyperglycemia (OR 2.10, 95% CI 1.30 to 3.37) in the past 12 months, long-term diabetes complications (OR 2.30, 95% CI 1.55 to 3.39) as well as currently having a diet plan (OR 2.14, 95% CI 1.39 to 3.29) than adults without depressive symptoms. Significant associations between depressive symptoms and other care indicators were not observed. Conclusions: The present population-based study of adults with diagnosed diabetes indicates an association between depressive symptoms and adverse diabetes-specific care with respect to outcome but largely not to process indicators. Our findings underline the need for intensified care for persons with diabetes and depressive symptoms. Future research needs to identify underlying mechanisms with a focus on the inter-relationship between diabetes, depression and diabetes-related distress.